Divinity compromised A study of divine accommodation in the thought of john calvin - Balserak, Jon.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book is the first monograph devoted to the theme of divine accommodation in the writings of John Calvin to appear in any language. The work offers careful analysis of the topic along several different lines: it analyzes the character of Calvin$1 (Bs thinking on accommodation. It gives an account of the ways in which accommodation expresses itself in his writings. It probes the question of the penetration of accommodation into Calvin$1 (Bs theology and particularly its implications for his doctrine of God. And it compares Calvin$1 (Bs handling of accommodation with that of other exegetes in order to set his thinking in context. In pursuing these matters, Dr Balserak provides a rigorous consideration of many of the individual places in Calvin$1 (Bs corpus where he discusses accommodation. This enables him to set out a summary of the basic qualities which characterize Calvin$1 (Bs handling of the motif. The addition of chapters on the relationship of Calvin$1 (Bs thought on accommodation to his use of the potentia absoluta/ordinata distinction and on the influence of accommodation on his views on the truth and applicability of Scripture allows this study to examine its topic from different angles. This, coupled with the thoroughness of the author$1 (Bs analysis, results in a work which offers a substantial reassessment of Calvin's thinking on divine accommodation.s
Divine accommodation in the tradition and calvin -- Human captus -- God's accommodating responses to human captus -- God's reasons for accommodating$1 (Bimages of god in calvin's handling of accommodation -- Accommodation and calvin'ng on the power of god -- The volatility of accommodation -- Concluding reflections.s
Keywords: Religion; Religious Studies; Religious Studies, general; Electronic books